PROJECT MANAGEMENT FOR STRENGTHENING STUDENT PROFILES PANCASILA IN EDUCATIONAL LEARNING ISLAMIC RELIGION AND CIVIL CIVIL PHASE E CURRICULUM INDEPENDENCE - Tamam, Badrut; Kadi, Titi; Fadhilah, Lisa Nurul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Strengthening the Pancasila student profile is a challenge for institutions education in producing young people who have character and values strong value. One effort to increase the profile of Pancasila students can be done through the implementation of projects in educational subjects Islamic religion and character. This research aims to analyze implementation of the project to strengthen the profile of Pancasila students in subjects Islamic religious education and character education for class X at SMK Negeri 10 Samarinda and its impact on improving the character of students. This research using a qualitative approach with data collection techniques through interviews, observations, and documentation. The research results show that The implementation of the project to strengthen the profile of Pancasila students was carried out with integrating Pancasila values into learning materials, as well as holding activities that help students understand and apply Pancasila values. The implementation of this project also had an impact positive towards improving the character of students, especially in terms of awareness of the importance of Pancasila values in everyday life. In conclusion, the implementation of the project strengthens the profile of students in Pancasila Islamic religious education and character subjects in class X at State Vocational Schools 10 Samarinda can help improve the character of students and make a positive contribution to the formation of a young generation has a strong Pancasila profile